Recurrent acute bilateral cicatricial conjunctivitis as an adverse event of systemic adalimumab for rheumatoid arthritis - Matsou, Artemis; Zormpas, Sokratis; Antunes, Diandra; McElvanney, Andrenna (Digital Journal of Ophthalmology, 2026)
Anti-TNF-α therapies, though known for their anti-inflammatory effects, have been associated with paradoxical inflammatory reactions, of which anterior uveitis is the most common. We report a case of recurrent bilateral cicatricial conjunctivitis linked to systemic adalimumab (ADA) treatment in a 66-year-old man with rheumatoid arthritis (RA). The patient experienced worsening bilateral red eyes, blurry vision, and discomfort following each ADA injection. Examination revealed signs of cicatricial inflammation, which responded to corticosteroids but recurred after subsequent ADA doses. Despite these ocular events, adalimumab was continued due to its effective control of systemic RA, with close ophthalmic monitoring. This case suggests a potential direct association between ADA and cicatricial conjunctivitis, a previously undescribed complication. Aggressive topical corticosteroid treatment may allow the continuation of ADA without compromising systemic disease control.